PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 5 SD N 03 BERINGIN - Vovi Tridian Ulfah; Jesi Alexander Alim; Zetra Khainul Putra (Universitas Teknokrat Indonesia, 2026)
Mathematics is one of the subjects taught in elementary schools that continues to face various challenges in its implementation. These challenges range from the widespread perception that mathematics is a difficult subject to the selection of appropriate teaching methods and instructional media for 21st-century learning. The background of this study stems from students' low understanding of mathematical concepts, which is caused by conventional teaching methods that are often less engaging and less effective in facilitating conceptual understanding. This study aims to determine the effect of using animated video media on the mathematics learning outcomes of fifth-grade students at SD N 03 Beringin. The research is motivated by students’ low learning interest and difficulties in understanding abstract mathematical concepts when taught solely through conventional methods. The novelty of this study lies in the integration of Animaker-based animated video media, a contextual learning approach that connects word problems to students’ daily lives, and a focus on fraction operations, which are considered one of the most complex mathematics topics in elementary education. This research employed an experimental method using a pretest-posttest control group design. The participants were fifth-grade students divided into an experimental class and a control class, with 23 students in each group. The research instrument consisted of a learning achievement test administered before and after the treatment. The results revealed a significant difference between the learning outcomes of students in the experimental class, which utilized animated video media, and those in the control class, which received conventional instruction. The average posttest score of the experimental class was higher than that of the control class, and statistical analysis indicated a positive effect of animated video media on improving mathematics learning outcomes. Therefore, it can be concluded that animated video media is effective in mathematics instruction, as it enhances students’ understanding of mathematical concepts and improves their learning outcomes..